2022
DOI: 10.1002/lary.30379
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Prescribing Trends After Major Pediatric Ear Surgery: A 12‐Year Analysis

Abstract: Objective Postoperative opioid prescriptions tend to exceed children's analgesic needs, but awareness of the opioid epidemic may have driven changes in prescribing behaviors. This study evaluated opioid prescribing patterns after major pediatric ear surgery. Methods This study reviewed all cases of tympanoplasty, tympanomastoidectomy, mastoidectomy, cochlear implantation, otoplasty, and aural atresia repair at a pediatric hospital during 2010–2021. Regressions were conducted to identify opioid prescribing tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…While it is clear that nonsurgical opioid prescription rates has decreased over time, opioid prescribing associated with surgery remains less well described. Recent publications found decreasing rates of opioid prescribing associated with specific pediatric surgeries at single academic institutions, including following major ear surgery and anterior cruciate ligament repair over the past decade 20,21 . However, a study by Donohue et al, found stable rates of opioid prescribing for pediatric outpatient surgery at a multispecialty children's hospital and freestanding surgery center 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is clear that nonsurgical opioid prescription rates has decreased over time, opioid prescribing associated with surgery remains less well described. Recent publications found decreasing rates of opioid prescribing associated with specific pediatric surgeries at single academic institutions, including following major ear surgery and anterior cruciate ligament repair over the past decade 20,21 . However, a study by Donohue et al, found stable rates of opioid prescribing for pediatric outpatient surgery at a multispecialty children's hospital and freestanding surgery center 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Hudgins et al found a small, but significant decrease in opioid prescribing for adolescent emergency department visits between 2005 and 2015 using data from the National Hospital Ambulatory Medical Care Survey and National Ambulatory Medical Care Survey 13. Using Optum Clinformatics Data Mart, a large commercial insurance provider dataset, Gagne et al showed that the mean monthly prevalence of outpatient opioid prescriptions per 1000 children or adolescents peaked at 5.8 in 2008 and steadily declined to 2.7 by 2017(20). However, this study was limited by only including private or commercial insurance holders which excludes a large subset of the pediatric population known to experience opioid management disparities-namely, uninsured patients and those paying out-of-pocket.…”
mentioning
confidence: 99%